Analisis Dampak Penggunaan Media Sosial TikTok terhadap Perkembangan Sosial Emosional Anak SD Usia 7-12 Tahun - Khoiru Rizqi Fitri Hadiyanur; Karina Amelia; Fahra Afthina; Nandria Elsya Syarif Hidayah; Dina Amalia (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The widespread use of TikTok across all age groups, including schoolchildren, has raised concerns regarding their social-emotional development. This study aims to analyze the impact of TikTok use on the social-emotional development of elementary school children aged 7-12. The study used a descriptive qualitative method. Data were collected through questionnaires with 17 students in the Jepara area, as well as questionnaires with 10 parents as supporting data. The results indicate that TikTok use has both positive and negative impacts. Positively, TikTok increases self-confidence, creativity, and facilitates conversation in social interactions. However, negatively, 64.7% of students use TikTok for more than two hours per day, 70.6% of children feel anxious if not accessing TikTok, and 47.1% experience sleep disturbances. Furthermore, the social-emotional aspect presents a serious challenge, with anger or irritation arising when usage time is limited. This study concludes that although children prioritize learning, the negative impact of TikTok on social-emotional learning requires active parental supervision.